PERAN KOMUNIKASI ANTAR PERSONA DALAM PELAKSANAAN 10 PROGRAM POKOK PKK - Hastuti, Nurnawati Hindra (Transformasi, 2012)
Abtract Communication is a process a massage from a communicator to communicant, so the communicant understand the meaning of the massage. Face to face ommunication is very effective to change the knowledge, opinion and attitude and behavior of people that dialogical meaning. Communication activity by TP.PKK in delivering messages about l0 main programs of PKK it can be known and understood ,so it can increase the knowledge and skills of women of PKK about variety foods ,and taking care of healthy and clean of environment. Keyword: Communication inter personal; behavior of people; opinion and attitude